Earthquake-triggered submarine landslides in the St. Lawrence Estuary (Québec, Canada) during the last two millennia and the record of the major 1663 CE M ≥7 event. (1st September 2022) - Mérindol, Méril; St-Onge, Guillaume; Sultan, Nabil; Lajeunesse, Patrick; Garziglia, Sébastien
Abstract: In eastern Canada, the Charlevoix-Kamouraska/Bas-Saint-Laurent (CKBSL) seismic zone presents a seismic hazard almost as high as that of the active Pacific zone. The major event of February 5, 1663 CE, with an estimated magnitude of ≥7, highlights the importance of this seismic hazard. The numerous submarine landslides mapped in the St. Lawrence Estuary in the CKBSL seismic zone suggest that earthquakes triggered series of submarine slope failures. In this context, the SLIDE-2020 expedition on board the RV Coriolis II in the St. Lawrence Estuary aimed to map, image and sample more than 12 zones of submarine instabilities and their associated deposits. The analysis of sediment cores sampled in the distal sedimentary deposits from these landslides reveals the presence of rapidly deposited layers (turbidites, hyperpycnites and debrites) directly linked to the submarine landslides. Dating these landslides with 210 Pb and 14 C techniques led to the identification of four periods of synchronous submarine landslides corresponding to the strongest historical earthquakes: 1663 CE, 1860/1870 CE, 1925 CE and 1988 CE (M ≥ 7, M = 6.1/6.6, M = 6.2, M = 5.9). This synchronicity over a distance reaching 220 km of several landslides supports a relationship between their triggering in the St. Lawrence Estuary and regional seismicity. The fact that as many as nine submarine landslides appear to have been triggered by the 1663 CE earthquake suggests that this event is the strongest recorded in the last two millennia in the region. Highlights: Submarine landslides distributed over 220 km in the St. Lawrence Estuary were dated. Submarine landslide deposits are synchronized to major historical earthquakes. Two older coeval submarine landslide deposits were dated around 645 and 1145 CE The 1663 CE event appears to be the strongest earthquake of the last 2000 years.